THE USE OF SOCIAL MEDIA IN INTERCULTURAL FRIENDSHIP DEVELOPMENT - Durrotul Mas'udah (Profetik: Jurnal Komunikasi, 2017)
ABSTRACT. Studying in a foreign country provides an opportunity for students from diverse cultural backgrounds to develop an intercultural friendship between each other. In today’s increasingly digitalized society, the use of social media cannot be detached from any communication context, including intercultural communication. Previous studies have examined the use of social media in various settings of intercultural communication. This study aims to examine the use of social media in intercultural friendship development among foreign students in Kocaeli University, Turkey. Applying qualitative method, six foreign students who represent four different cultural backgrounds were interviewed in this study. The interview tried to explore their subjective experiences of using social media to develop an intercultural friendship with other foreign students in their surroundings. The study reveals various similarities and differences of the pattern, evaluation, and impact of using social media in intercultural friendship development. The study concludes that the use of social media tends to enhance the intercultural friendship development.